A review on two-dimensional (2D) perovskite material-based solar cells to enhance the power conversion efficiency. Issue 3 (7th December 2021) - Elahi, Ehsan; Dastgeer, Ghulam; Siddiqui, Abdul Subhan; Patil, Supriya A.; Iqbal, Muhammad Waqas; Sharma, Pradeep Raj
Abstract : With perovskite materials, rapid progress in power conversion efficiency (PCE) to reach 25% has gained a significant amount of attention from the solar cell industry. Abstract : With perovskite materials, rapid progress in power conversion efficiency (PCE) to reach 25% has gained a significant amount of attention from the solar cell industry. Since the development of solid-state perovskite solar cells, rapid research development and investigation on structure design, device fabrication and fundamental studies have contributed to solid-state perovskite solar cells to be a strong candidate for next-generation solar energy. The promising efficiency with low-cost materials is the key point over the other material-based solar cells. The power conversion efficiency (PCE) of two-dimensional (2D) perovskite materials is yet to be enhanced in order to contest with the 3D perovskite-based solar cells. Their enormous variety compromises better prospects and possibilities for research. Two-dimensional (2D) perovskites play a multi-functional role within a solar cell, such as a capping layer, passivating layer, prime cell absorber, and in a hybrid 3D/2D perovskite-based solar cell absorber. This review summarizes the evolution of solar cells that are based on 2D perovskites and their prominent character in solar cells, along with the significant trends. The fundamental configuration and the optoelectronic characteristics, including the band orientation and the transportation of the charges, are discussed in detail. The 2D perovskites are analyzed to study the confined charges within the inorganic structure due to the dielectric and quantum confinement influence. Furthermore, the importance of cesium cation (Cs + ) doped with 2D substance (BA)2 (MA3 ) PbI3 approach has been discussed to attain high power conversion efficiency (PCE). These attributes offer an efficient step towards air-stable and small-sized perovskites as a new group of renewable energy sources.